Bacterial Dispersal Promotes Biodegradation in Heterogeneous Systems Exposed to Osmotic Stress - Worrich, Anja; König, Sara; Banitz, Thomas; Centler, Florian; Frank, Karin; Thullner, Martin; Harms, Hauke; Miltner, Anja; Wick, Lukas Y.; Kästner, Matthias (Frontiers in Microbiology, 2016)
Contaminant biodegradation in soils is hampered by the heterogeneous distribution of degrading communities colonizing isolated microenvironments as a result of the soil architecture. Over the last years, soil salinization was recognized as an additional problem especially in arid and semiarid ecosystems as it drastically reduces the activity and motility of bacteria. Here, we studied the importance of different spatial processes for benzoate biodegradation at an environmentally relevant range of osmotic potentials (ΔΨo) using model ecosystems exhibiting a heterogeneous distribution of the soil borne bacterium Pseudomonas putida KT2440. Three systematically manipulated scenarios allowed us to cover the effects of i) substrate diffusion ii) substrate diffusion and autonomous bacterial dispersal, and iii) substrate diffusion and autonomous as well as mediated bacterial dispersal along glass fiber networks mimicking fungal hyphae. To quantify the relative importance of the different spatial processes, we compared these heterogeneous scenarios to a reference value obtained for each ΔΨo by means of a quasi optimal scenario in which degraders were ab initio homogenously distributed. Substrate diffusion as the sole spatial process was insufficient to counteract the disadvantage due to spatial degrader heterogeneity at ΔΨo ranging from 0 to 1 MPa. In this scenario, only 13.8 to 21.3 % of the quasi-optimal biodegradation performance could be achieved. In the same range of ΔΨo values, substrate diffusion in combination with bacterial dispersal allowed between 68.6 % and 36.2 % of the performance showing a clear downwards trend with decreasing ΔΨo. At ¬ 1.5 MPa, however, this scenario performed worse than the diffusion scenario, possibly as a result of energetic disadvantages associated with flagellum synthesis and emerging requirements to exceed a critical population density to resist osmotic stress. Network mediated bacterial dispersal kept biodegradation almost consistently high with an average of 70.7 ± 7.8 %, regardless of the strength of the osmotic stress. We propose that especially fungal network mediated bacterial dispersal is a key process to achieve high functionality of heterogeneous microbial ecosystems also at reduced osmotic potentials. Thus, mechanical stress by, for example, soil homogenization should be kept low in order to preserve fungal network integrity.